DETERMINANT OF INDONESIAN GOVERNMENT BOND ‘YIELD’ IN DOMESTIC PRIMARY MARKET - Bahtiar Usman; Febrianto Dias Chandra; Syofriza Syofyan (Media Ekonomi, 2020)
This study aims to analyze determinants which might influenced yield of Indonesian Government Bond Denominated-Rupiah in primary market. We divide the determinant by three factors (i.e intrinsic factor, extrinsic domestic factor and extrinsic globar factor). Multiple regression using to analyze colinearity among variables in this study. The results showed that bond maturity, bond coupon rate, bond price in secondary market, bond performance in market, inflation rate, currency, money and stock domestic market condition, and money and bond global market condition are significantly affected Indonesian government bond yield in primary market.